2004
DOI: 10.1021/bi048632b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Time-Dependent Inhibition of Polypeptide Deformylase by Actinonin

Abstract: Polypeptide deformylase (PDF) is an essential bacterial metalloenzyme responsible for the removal of the N-formyl group from the N-terminal methionine of nascent polypeptides. Inhibition of bacterial PDF enzymes by actinonin, a naturally occurring antibacterial agent, has been characterized using steady-state and transient kinetic methods. Slow binding of actinonin to these enzymes is observed under steady-state conditions. Progress curve analysis is consistent with a two-step binding mechanism, in which tight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 22 publications
5
48
0
Order By: Relevance
“…Here, we have provided strong evidence that PDF is the molecular target of PDF inhibitors, particularly BB-3497, with anti-L. pneumophila activity. As described for other bacterial species (35), both actinonin and BB-3497 exhibit time-dependent inhibition of all three L. pneumophila PDFs, with slow rates of dissociation from the enzymes. While the structural basis for time dependency is undefined at present, it is clear that the net effect of this time-dependent process is a significant potency increase ranging from 20-to 160-fold, comparing K i to K i *.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Here, we have provided strong evidence that PDF is the molecular target of PDF inhibitors, particularly BB-3497, with anti-L. pneumophila activity. As described for other bacterial species (35), both actinonin and BB-3497 exhibit time-dependent inhibition of all three L. pneumophila PDFs, with slow rates of dissociation from the enzymes. While the structural basis for time dependency is undefined at present, it is clear that the net effect of this time-dependent process is a significant potency increase ranging from 20-to 160-fold, comparing K i to K i *.…”
Section: Discussionsupporting
confidence: 64%
“…Time-dependent inhibition of PDF has been reported previously (15,26,35) and is best described by a two-step mechanism in which the initial encounter complex, EI, tightens to form EI* with a slow off rate (k 6 ).…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Q57 is part of a conserved region present only in class II enzymes, and V71 is located within the highly conserved motif 1, which is involved in the structural stability and catalytic mechanism of PDF. It has been shown that PDF inhibitors such as GSK1322322 display strong time-dependent inhibition, which contributes to their antibacterial potency (32). Recent kinetic studies support the hypothesis that the time-dependent nature of PDF inhibition is due to both the binding of the compounds to the active site metal of PDF and the hydrogen-bonding network between the inhibitor and certain key residues of the protein, including V71 (33).…”
Section: Discussionmentioning
confidence: 99%